Gastrointestinal Stromal Tumour: cause of Obscure Gastrointestinal Bleeding. - Ngow, Harris Abdullah; Wan Mohd Nowalid, Wan Khairina (Ambit Media, a. s., 2010)
Gastrointestinal stromal tumours (GISTs) are rare tumours. It can cause occult gastrointestinal bleeding when conventional investigations fail to detect the bleeding lesions. Obscure gastrointestinal bleeding also represents a challenge in the quest for the clinical diagnosis and its therapeutic approach. We report a case of gastrointestinal bleeding originated from small bowel gastrointestinal stromal tumour diagnosed by capsule endoscopy and computerized tomography (CT) imaging. This case illustrates the difficulty in diagnosing GISTs and the important role of capsule endoscopy as a non-invasive investigation modality. The treatment options include curative surgical resection and tyrosine kinase inhibitor.